2021
DOI: 10.1108/jeee-09-2020-0334
|View full text |Cite
|
Sign up to set email alerts
|

Who really acts as an entrepreneur in the science commercialisation process: the role of knowledge transfer intermediary organisations

Abstract: Purpose Consistent with the knowledge spillover theory of entrepreneurship, the purpose of this paper is to recognise the complementary entrepreneurial role of knowledge transfer intermediary organisations in the context of two Central and Eastern European (CEE) countries: Poland and the Czech Republic. Design/methodology/approach The aim was achieved through empirical studies relying on multiple-case study methodology and cross-case analysis covering 21 cases of commercialisation intermediary institutions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…He explains that intermediary action includes “helping to provide information about potential collaborators; brokering a transaction between two or more parties; acting as a mediator, or go-between, of bodies or organizations that are already collaborating; and helping find advice, funding and support for the innovation outcomes of such collaborations”. Several types or forms of innovation intermediaries have been discussed in the literature as IOs, including technology transfer offices, technology licensing organisations, university incubators, intellectual property headquarters, university-based venture development organisations and cooperative research centres (Szulczewska-Remi and Nowak-Mizgalska, 2021; Villani et al, 2017). Cluster initiatives can also act as IOs between different stakeholders in cluster settings and within the open innovation framework, as in the Triple Helix and Quadruple Helix models (Klofsten et al, 2015; Laur et al, 2012).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…He explains that intermediary action includes “helping to provide information about potential collaborators; brokering a transaction between two or more parties; acting as a mediator, or go-between, of bodies or organizations that are already collaborating; and helping find advice, funding and support for the innovation outcomes of such collaborations”. Several types or forms of innovation intermediaries have been discussed in the literature as IOs, including technology transfer offices, technology licensing organisations, university incubators, intellectual property headquarters, university-based venture development organisations and cooperative research centres (Szulczewska-Remi and Nowak-Mizgalska, 2021; Villani et al, 2017). Cluster initiatives can also act as IOs between different stakeholders in cluster settings and within the open innovation framework, as in the Triple Helix and Quadruple Helix models (Klofsten et al, 2015; Laur et al, 2012).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…In addition, other competences can be supplemented by knowledge transfer intermediary organizations, especially complementary resources needed for commercial exploitation of opportunity like laboratory equipment, office space, information technology infrastructure or access to financial resources. Szulczewska-Remi and Nowak-Mizgalska (2021), in the aforementioned work, based on Polish and Czech studies, showed that other entrepreneurial competences are provided by these intuitions, mainly evaluation of an invention's commercialisation potential, team building and business model development.…”
Section: The Entrepreneurial Competences As Value Driversmentioning
confidence: 99%
“…After the patenting phase, technologies can be licensed and sold commercially (Harryson, 2008;Kamariah et al, 2011;Szulczewska-Remi & Nowak-Mizgalska, 2021). The existing evidence on the benefits of AI for precision psychiatry, however, does not take into account factors that are relevant for market adoption (e.g., Bzdok & Meyer-Lindenberg, 2018;Passos et al, 2022;Salazar de Pablo et al, 2021;Zanardi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%